Information Science and Information Systems: Converging or Diverging? - Monarch, Ira A (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Recent studies have claimed a disconnect between the disciplines of information science and information systems even though, prima facie, there seems to be considerable overlap or potential overlap in their respective subject matter. The present study will target representative journals in the areas of information science and information systems and examine in more detail the overlap or lack of overlap between the two fields as reflected in the co-word analysis of the titles and abstracts of these journal articles. That the subject matters of the two fields can be combined in a discipline will be shown by a similar analysis of a third field, medical informatics, a new discipline in it its own right and a seeming subject matter hybrid of information science and information systems.